The cult of statistical significance. What economists should and should not do to make their data talk - Walter Krämer (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2011)
This article takes issue with a recent book by Ziliak and McCloskey (2008) of the same title. Ziliak and McCloskey argue that statistical significance testing is a barrier rather than a booster for empirical research in economics and should therefore be abandoned altogether. The present article argues that this is good advice in some research areas but not in others. Taking all issues which have appeared so far of the German Economic Review and a recent epidemiological meta-analysis as examples, it shows that there has indeed been a lot of misleading work in the context of significance testing, and that at the same time many promising avenues for fruitfully employing statistical significance tests, disregarded by Ziliak and McCloskey, have not been used.
Keywords: 330; Statistischer Test; Kritik; Statistische Methodenlehre; Theorie